Study of Electrical Systems in Engineering Faculty Udayana University Bukit Jimbaran - Janardana, I G. N.; Wijaya, W. Arta (Journal of Electrical, Electronics and Informatics; Vol 3 No 2 (2019): JEEI (August 2019), 2020)
Electrical systems that serve the Dean of electricity load, the electricity load of the Departement of Architecture, Departement of Mechanical Engineering, Departement of Electrical Engineering, Departement of Information Technology, external lighting facilities supplied by transformers with a capacity of 200 KVA. Lately the quality electrical system has begun to decline with frequent interruptions such as the breakdown of electricity to the load, unbalanced load, THD current exceeds the standard, the fuse on the incoming to the parent panel and the fuse on the main panel is often burned, the grounding system resistance value exceeds the standard equipment value, cable temperature exceeds the standard, even voltage rises to 500 volts. The purpose of this study is to determine the causes of disruption of electricity, and produce a new master installation design to improve the system. Based on the results of the analysis, it was found that the importance of channel separation between loads to the Dean building with the Departement of Architecture building with cable capacity for the Dean building of NYY 4 x 95 mm2 and the safety of the NFb 200 Ampere mains. For cables to the building load, the Departement of Architecture installed a new main cable with NYY 4 x 50 mm2 cable size and NFb 150A main safety. It is necessary to replace the main NFb safety at the MDP parent panel which supplies the load to the Departement of Mechanical Engineering building from 160 Ampere to 200 Ampere. The entire phase in each panel does not meet the IEEE 519 - 2014 standard, so it is very important to install a filter. Ground resistance values ??on all panels vary above the standard with a value of 12 to 62 ohms. So it needs to be made a new grounding. When using a plate grounding system, the number of plates that need to be planted is 25 sheets with a size of 2m x 1 m with a planting depth of 2 m. Whereas when using a grid type earth system, a grid with a size of 3 meters x 3 meters is needed with a total grid length of 2976 meters and a depth of 3 meters.